THU0150 Optimizing comorbidity risk management in ra by translating a nurse-led interview into an easily interpretable traffic light system. (15th June 2017) - Krüger, K; Eder, R; Müller, C; Hecker, R
Abstract : Background: Due to its inflammatory nature, rheumatoid arthritis (RA) is associated with a variety of comorbidities and individual risk factors [1]. The benefit of a nurse-led programme on RA comorbidity management has been reported recently [2]. Objectives: To describe a new assessment tool for patient risk management and report the difference between structured versus expert guided assessment following standard of care in a construct-validation cohort. Methods: The ongoing cluster randomized multicentre study ERIKO is longitudinally assessing individual risk profiles of patients with RA in Germany. The aim of this study is to test the benefit of applying a nurse-led scoring algorithm for individual risk profiles followed by a structured patient consultation (active arm) as compared to local standard of care. The ERIKO-Score was calculated by rating validated assessment tools and treatment guidelines and translating their outcome into a three-level ordinal score defined by the categories low, intermediate or high risk, including nominal weights for risk management (e.g. condition is being treated with goals achieved or not). Scores were interpreted numerically by rating categories with 0, 1 and 2 points, respectively. We included cardiovascular (CV) risk (ESC-guideline), infection risk (RABBIT risk calculator), vaccination status (guideline), fracture risk (FRAX), tooth status (PSI), depression- (PHQ-9) and health-related quality of life (hrQoL, RAID). The same risk categorization was prompted in all centres at the screening visit without providing the rating tools. This analysis compares SOC ratings from the screening visit (month zero) with the baseline ERIKO-scores at month three in the active arm. No statistical hypothesis testing was performed in this analysis. Results: This analysis included 283 patients from 31 centres specialized in rheumatology care randomized to the active study arm. 82.3% were female with a mean age of 57.8 years (sd 12.1) and a mean DAS28 of 2.6 (sd 1.1). The mean total ERIKO-Score was slightly higher at baseline as compared to applying the scoring algorithm on SOC ratings at the screening visit (5.33 +- 1.95 vs. 4.32 +- 2.61, respectively, table 1 ). The discrepancy was mainly driven by CV risk, vaccination status, tooth status and depression risk, that were more often rated worse by applying the ERIKO score than by SOC, while infection- and fracture risk were more frequently rated lower by the ERIKO-Score (table 2). The strongest discrepancy between SOC ratings and ERIKO-Score (Δ =2 points) were observed for tooth status (N=54), CV risk (N=25) and vaccination status (N=25) (table 2). SOC ratings were strongly based on expert opinion with the most frequently cited tools being vaccination guidelines (38.9%), bone mineral density measurement (BMD) (39.6%) and RABBIT-infection risk-score (23.1%). Conclusions: A nurse-led comorbidity risk assessment in rheumatology practices seems feasible. Applying the ERIKO-Score based on validated tools led to a higher risk grading than the predominantly expert-opinion based SOC. Construct validation of the ERIKO-Score is ongoing. References: Dougados M, et al. Ann Rheum Dis 2014;73:62–8. Dougados M, et al. Ann Rheum Dis 2015;74:1725–33. Acknowledgements: We are grateful to Dr. Imma Fischer (Tübingen) for statistical support. Disclosure of Interest: K. Krüger Consultant for: AbbVie Deutschland GmbH & Co. KG, Speakers bureau: AbbVie Deutschland GmbH & Co. KG, R. Eder Consultant for: AbbVie Deutschland GmbH & Co. KG, C. Müller Shareholder of: Abbvie Inc., Employee of: AbbVie Deutschland GmbH & Co. KG, R. Hecker Shareholder of: Abbvie Inc., Employee of: AbbVie Deutschland GmbH & Co. KG